International Youth Camp promotes patriotic spirit among youth - Nurhaslina, Mohamad Radzi; Siti Nurfarmy, Ibrahim (https://news.ump.edu.my/index.php/general/international-youth-camp-promotes-patriotic-spirit-among-youth, 2023)
JOHOR BAHRU, 17 September 2023 – A total of 190 youths, including students from various public and private higher education institutions (IPTA/IPTS) and recent graduates up to the professional level, gathered to enliven the International Youth Camp (IYC) held at Universiti Teknologi Malaysia (UTM), Johor Bahru from September 17 to 19 recently.